Vibrio vulnificus necrotizing fasciitis associated with acupuncture - Yael Kotton; Soboh Soboh; Naiel Bisharat (MDPI AG, 2015)
Necrotizing fasciitis is a severe life-threatening infection of the deep subcutaneous tissues and fascia. Infection with Vibrio vulnificus, a halophilic Gram-negative bacillus found worldwide in warm coastal waters, can lead to severe complications, particularly among patients with chronic liver diseases. We herein present an unusual case of necrotizing fasciitis caused by V. vulnificus triggered by acupuncture needle insertion. The patient, who suffered from diabetes mellitus and non-alcoholic fatty liver disease and worked at a fish hatchery, denied any injury prior to acupuncture. This is the first ever reported case of V. vulnificus infection triggered by acupuncture needle insertion, clearly emphasizing the potential hazards of the prolonged survival of V. vulnificus on the skin. The potential infectious complications of acupuncture needle insertion are discussed.